Analisis Seismisitas Wilayah Turki sebagai akibat Aktivitas Seismo-Tektonik Patahan Anatolia - Dewi, Karlita; Fahmi, Muhammad Nurul; Realita, Arie (Inovasi Fisika Indonesia, 2025)
This study aims to analyze the seismicity and tectonic stress in Turkey based on earthquake data from the period 1924–2024 using the Frequency-Magnitude Distribution (FMD) approach with the ZMAP7.0 software. The study area is divided into four zones: Zone 1 (northwestern Turkey), Zone 2 (northeastern Turkey), Zone 3 (southwestern Turkey), and Zone 4 (southeastern Turkey). The parameters analyzed include the a-value for seismicity levels and the b-value for estimating subsurface tectonic stress. The results show that a-values ranging from approximately 5.80 to 6.03 are higher in Zones 3 and 4, indicating more frequent seismic activity in the southern regions. Conversely, Zones 1 and 2 have lower a -value, indicating less frequent earthquake occurrences. Lower b-value were found in the northern regions 0.58–0.66, suggesting higher tectonic stress and a greater potential for large earthquakes, particularly along the North Anatolian Fault. The southern regions exhibit higher b-values, reflecting lower stress levels and predominantly smaller earthquakes. For intermediate-depth sources, analysis was conducted only in Zone 3, where a low b-value indicates the potential for large earthquakes at these depths. This study contributes to a better understanding of Turkey's seismic characteristics and is essential for earthquake disaster mitigation planning.